Development of Micropropagation Protocol in Simmondsia chinensis (Link) Schneider - Reddy, Veena; M, Srikanth Reddy; Kumar, S Manoj; Naresh, B; Kumar, B Kiran; Devi, B Rama; Cherku, Prathibha Devi (Plant Tissue Culture and Biotechnology, 2017)
Abstract not available Plant Tissue Cult. & Biotech. 27(1): 77-83, 2017 (June)